Staphylococcus aureus and CA-MRSA Carriage among Brazilian Indians Living in Peri-Urban Areas and Remote Communities - Abraão, Lígia Maria [UNESP]; Fortaleza, Carlos Magno Castelo Branco [UNESP]; Camargo, Carlos Henrique; Barbosa, Thaís Alves [UNESP]; Pereira-Franchi, Eliane Patrícia Lino [UNESP]; Riboli, Danilo Flávio Moraes [UNESP]; Hubinger, Luiza [UNESP]; Bonesso, Mariana Fávero [UNESP]; Medeiros de Souza, Rodrigo; Ribeiro de Souza da Cunha, Maria de Lourdes [UNESP] (MDPI, 2023)
The emergence of Community-associated methicillin-resistant Staphylococcus aureus (CA-MRSA) infections among indigenous populations has been reported. Usually, indigenous communities live in extreme poverty and are at risk of acquiring infections. In Brazil, healthcare inequality is observed in this population. To date, there are no reports of CA-MRSA infections, and no active search for asymptomatic S. aureus carriage has been conducted among Brazilian Indians. The aim of this study was to investigate the prevalence of colonization with S. aureus and CA-MRSA among Brazilian Indians. We screened 400 Indians (from near urban areas and remote hamlets) for S. aureus and CA-MRSA colonization. The isolates were submitted to clonal profiling by pulsed-field gel electrophoresis (PFGE), and selected isolates were submitted to multilocus sequence typing (MLST). Among 931 specimens (nasal and oral) from different indigenous individuals in remote hamlets, S. aureus was cultured in 190 (47.6%). Furthermore, CA-MRSA was found in three isolates (0.7%), all SCCmec type IV. PFGE analysis identified 21 clusters among the S. aureus isolates, and MLST analysis showed a predominance of sequence type 5 among these isolates. Our study revealed a higher prevalence of S. aureus carriage among Shanenawa ethnicity individuals (41.1%). Therefore, ethnicity appears to be associated with the prevalence of S. aureus in these populations.
Keywords: brazilian indians; CA-MRSA; colonization; ethnicity; remote communities; Staphylococcus aureus